Principles of Developing “V-I-S-U-A-L-S” Media in Teaching English to Young Learners at SD GMIT Oepura - Hambandima, Erny Selfina Nggala; Seseli, Eka Merdekawati Imelda (ETERNAL (English Teaching Journal), 2025)
Abstract. This research aims to help EYL teachers utilize the media to achieve learning goals. The learning process becomes fun, students are pro-active in learning, the material is easy to understand and there is interaction between teachers and students. The research was conducted in the SD GMIT Oepura, where the researcher taught the elementary students using EYL media which EYL students have made. This focuses on how the elementary students respond to the media itself whether the media interacted with them or not. The research data was collected through observation. Analysis was carried out through analytical descriptive methods and qualitative content analysis. Research on this topic is about V-I-S-U-A-L-S which stands for visible, interesting, simple, useful, accurate, legitimate, and structured, was obtained from (1.) Media create a memorable learning experience, understand complex and abstract concepts through colorful images, grab attention, and encourage active participation. (2.) Psychologically, the v-i-s-u-a-l-s media development provides meaningful experiences, and builds the young learners’ creativity by overcoming limitations of time, space, and energy that make the learning more interactive, improving the quality of their learning outcomes. (3.) V-i-s-u-a-l-s media helps students understand difficult material, making the learning process more interesting and varied, and making students more active in class. (4.) V-i-s-u-a-l-s media builds students’ creativity to develop their interaction easily between teachers and students so that learning activities are more effective and efficient. (5.) V-i-s-u-a-l-s media stimulated young learners to learn more actively. (6.) V-i-s-u-a-l-s media helps the teaching and learning process with various benefits, such as reducing obstacles in the learning process, assisting teachers in providing explanations of learning material, helping students absorb lesson material more deeply, helping students think concretely, and helping students build creativity.